Business model for cross-border interconnections in the Mediterranean basin. (August 2017) - Poudineh, Rahmatallah; Rubino, Alessandro
Abstract: Given the complementarity of electricity systems in the north and south Mediterranean basin, a greater integration and trade can help achieving national and regional energy policy objectives of security of supply, cost optimisation and sustainability. However, the issues such as different electricity market structures, regulatory and institutional diversity and disparate level of political stability make interconnection investment between north and south a risky undertaking. Due to high perceived risk, delivery of interconnection projects through the EU regulated model is less likely, or only possible at prohibitively high rate of returns. The merchant transmission initiative (MTI), on the other hand, seen as an exception under the EU laws, can be approved only if the project meets a set of strict conditions. Here we show that a hybrid business model in which the main benefits of a merchant model are maintained within a regulated structure, that involves minimal regulatory changes to national electricity markets, offers an appropriate response to the existing investment challenges in the Euro-Mediterranean basin. We highlight the main components of the proposed model and show how it addresses the key features of a viable business model regarding investment incentives, risks, governance and compatibility with the region's energy scenario. Highlights: The existing Mediterranean interconnections are driven by national policies. Now national dynamics must be harmonised with regional and global developments. MED-TSO is expecting to construct an additional 33, 000 km of high voltage lines. Neither a regulated model nor MTI can ensure greater integration in the region. A hybrid business model is a better response to the existing investment challenges.